Strategi Penentuan Harga dalam Pemasaran Jasa Pendidikan - Ramdhani, Ratna Dwi; Jarya, Haenul; Patimah, Siti Nur; Ifendi, Mahfud (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
Pricing in marketing educational services is one of the important aspects that affect the competitiveness and sustainability of educational institutions. This study aims to analyze cost-based, value-based, and competition-based pricing strategies in the education sector in Indonesia. A qualitative approach with a library research method is used to identify various relevant pricing techniques and their impact on the attractiveness of educational institutions. The results of the study indicate that a combination of cost-based and value-based strategies has great potential in improving the financial sustainability of institutions while strengthening the perception of quality in the eyes of consumers. These findings provide practical implications in the form of guidelines for educational institution managers to set competitive, relevant, and market-needed prices. By implementing the right techniques, educational institutions can improve financial sustainability and attractiveness to prospective students, as well as maintain competitiveness in the competitive education market.